Improving Consumer Welfare and Manufacturer Profit via Government Subsidy Programs: Subsidizing Consumers or Manufacturers? - Yu, Jiayi Joey; Tang, Christopher S.; Shen, Zuo-Jun Max (Manufacturing and Service Operations Management, 2018)
Most consumers in rural areas of many developing countries cannot afford to purchase certain livelihood improvement products such as home appliances. To improve consumer welfare and manufacturer profit, many governments launch different types of subsidy programs that offer subsidies to consumers, manufacturers, or both. Motivated by a subsidy program developed by the Chinese government in 2007, we present a parsimonious model to determine the optimal subsidy program in different settings so as to gain a better understanding about the conditions under which it is optimal for the government to subsidize consumers only, manufacturers only, or both. Our analysis reveals that the structure of the optimal subsidy program depends on (a) whether there is a well-established market selling price for the products; and (b) the relative emphasis that the government places on consumer welfare versus manufacturer profit. Also, we find that governments can improve consumer welfare by developing subsidy programs that involve multiple (competing) manufacturers with different market sizes and adequate capacities. Our findings provide insights for developing effective government subsidy programs. The online appendix is available at https://doi.org/10.1287/msom.2017.0684 .